Nutritional Status and Quality of Life in Shift Workers - Demirci, Ülkü; Kaptanoğlu, Ayşegül (Progress in Nutrition, 2022)
Background and aim: In individuals working in shifts, the risk of metabolic disorders and diseases is amplified due to irregular timing of the meal, quality of nourishment received from the diet, and inadequate sleep. In this survey, we studied the nutritional status and quality of life (QoL) among shift workers and the factors affecting these characteristics. Methods: An online survey was conducted among 137 adult participants working in shifts in the Beylikdüzü campus. The data were collected using the QoL assessment tool EQ-5D-5L questionnaire. Results: The mean score of EQ-5D-5L sub-dimensions, mobility (1.27±0.56); self-care (1.12±0.51); usual activity (1.14±0.42); pain-discomfort (1.43±0.69), and anxiety-depression (1.66±0.87) were low. In 48(35.8%) participants shift time deviated their mealtime. A total of 74 (54%) participants ate 2 meals during the day shift while 78(56%) ate 1 meal during the night shift. Conclusions: Working in shifts had a negative effect on mealtimes, nutrition, and meal frequency.